2021
DOI: 10.1007/s00787-021-01802-w
|View full text |Cite
|
Sign up to set email alerts
|

Longer-term effects of school-based counselling in UK primary schools

Abstract: Children's mental health is deteriorating while access to child and adolescent mental health services is decreasing. Recent UK policy has focused on schools as a setting for the provision of mental health services, and counselling is the most common type of school-based mental health provision. This study examined the longer-term effectiveness of one-to-one school-based counselling delivered to children in UK primary schools. Data were drawn from a sample of children who received schoolbased counselling in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Ten evaluations were conducted with learners in primary schools (Cooper, Stafford, et al, 2021; Cooper, Stewart, et al, 2013; Daniunaite et al, 2015; Economics PB, 2018; Finning et al, 2021; Lee et al, 2009; McArdle et al, 2002; Sherr et al, 1999; Sherr & Sterne, 1999). The one RCT conducted with learners primarily in primary school found that, after 12 weeks, learners participating in both group therapy and curriculum studies groups reported reduced problem behaviours (McArdle et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten evaluations were conducted with learners in primary schools (Cooper, Stafford, et al, 2021; Cooper, Stewart, et al, 2013; Daniunaite et al, 2015; Economics PB, 2018; Finning et al, 2021; Lee et al, 2009; McArdle et al, 2002; Sherr et al, 1999; Sherr & Sterne, 1999). The one RCT conducted with learners primarily in primary school found that, after 12 weeks, learners participating in both group therapy and curriculum studies groups reported reduced problem behaviours (McArdle et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The feasibility cluster randomised design did not show a significant improvement in the SDQ measurements (Cooper, Duncan, et al, 2021). Both of the nonrandomised controlled evaluations (Finning et al, 2021; Sherr & Sterne, 1999) and four of the pre‐ and poststudy designs (Daniunaite et al, 2015; Economics PB, 2018; Lee et al, 2009; Sherr et al, 1999) related to school counselling provided by the charity organisation Place2Be. All of the studies found an improvement in mental health using either parent or teacher reporting (Finning et al, 2021), learner reporting (Sherr & Sterne, 1999), counsellor reporting (Sherr et al, 1999) or the SDQ measurement (Daniunaite et al, 2015; Economics PB, 2018; Lee et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If needed, additional information from teachers could be obtained. The use of multi-informants could prove beneficial, as a high burden of care and mental health challenges have been described in these families, increasing the risk of psychopathology [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%